Archaeology under fire : nationalism, politics and heritage in the eastern Mediterranean and Middle East - Meskell, Lynn (Routledge, 1998)
Archaeology Under Fire addresses archaeology's role in current political issues, including the ethnic cleansing in the Balkans, the division of Cyprus, and the continued destruction of Beirut.